2013
DOI: 10.1111/jrir.12010
|View full text |Cite
|
Sign up to set email alerts
|

The effects of musical training on the decoding skills of German‐speaking primary school children

Abstract: This paper outlines the results of a long-term study of 159 German-speaking primary school children. The correlations between musical skills (perception and differentiation of rhythmical and tonal/melodic patterns) and decoding skills, and the effects of musical training on word-level reading abilities were investigated. Cognitive skills and socioeconomic factors were controlled as covariates in all analysis. The experimental group received special musical training for 9 months. A comparison sample received al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 39 publications
1
33
1
Order By: Relevance
“…The hypothesis that musical training can enhance reading ability was tested as early as 1975 (Hurwitz et al, 1975) and has since been investigated in at least twenty-two separate studies. This work has ranged from cross-sectional comparisons of musicians and nonmusicians to longitudinal studies with random assignment of children to music training or control groups (for recent examples see Cogo-Moreira et al, 2013 and Rautenberg, 2013). Although there is a moderate degree of variability in the results reported, likely due to the heterogeneous nature of musical training, eighteen of the twenty-two studies reported that musical training increased reading or pre-reading abilities (for a review see Tierney and Kraus, 2013a).…”
Section: Musical Training and Readingmentioning
confidence: 99%
“…The hypothesis that musical training can enhance reading ability was tested as early as 1975 (Hurwitz et al, 1975) and has since been investigated in at least twenty-two separate studies. This work has ranged from cross-sectional comparisons of musicians and nonmusicians to longitudinal studies with random assignment of children to music training or control groups (for recent examples see Cogo-Moreira et al, 2013 and Rautenberg, 2013). Although there is a moderate degree of variability in the results reported, likely due to the heterogeneous nature of musical training, eighteen of the twenty-two studies reported that musical training increased reading or pre-reading abilities (for a review see Tierney and Kraus, 2013a).…”
Section: Musical Training and Readingmentioning
confidence: 99%
“…This contrasts with previous work, which has focused on atypical development (Weinert, ). We also examined the possible relation between rhythmic skills and phonological awareness, as suggested in past work examining the role of rhythm in learning to read (Anvari et al ., ; Forgeard et al ., ; Rautenberg, ).…”
Section: Introductionmentioning
confidence: 99%
“…This relation has been shown for children with and without music training. Higher levels of musical aptitude are associated with enhancement in a number of reading-related skills in children without formal music training (Anvari, Trainor, Woodside & Levy, 2002;Forgeard, Schlaug, Norton, Rosam & Iyangar, 2008;Strait, Hornickel & Kraus, 2011;Rautenberg, 2013). In the domain of musical rhythm, kindergarteners' rhythmic aptitude has been found to predict their second grade phonological awareness and word identification proficiency (Moritz, Yampolsky, Papadelis, Thomson & Wolf, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Reading ability and phonological awareness are related to a variety of rhythmic abilities, including reproduction of rhythmic patterns (e.g. Rautenberg, 2015), tempo reproduction (Moritz, Yampolsky, Papadelis et al, 2012); tapping to the beat of music (David, Wade-Woolley, Kirby and Smithrim, 2007); and discrimination of stimuli based on amplitude rise times (see Goswami, Wang, Cruz, et al 2011;Leong, Hamalainen, Soltesz and Goswami, 2011) and temporal patterns (e.g. Overy, 2003;Strait, Hornickel and Kraus, 2011).…”
Section: The Relationship Between Music and Languagementioning
confidence: 99%